Modelling Inequality. (27th February 2017) - Thébault, Karim; Bradley, Seamus; Reutlinger, Alexander
Abstract: Econophysics is a new and exciting cross-disciplinary research field that applies models and modelling techniques from statistical physics to economic systems. It is not, however, without its critics: prominent figures in more mainstream economic theory have criticized some elements of the methodology of econophysics. One of the main lines of criticism concerns the nature of the modelling assumptions and idealizations involved, and a particular target are 'kinetic exchange' approaches used to model the emergence of inequality within the distribution of individual monetary income. This article will consider such models in detail, and assess the warrant of the criticisms drawing upon the philosophical literature on modelling and idealization. Our aim is to provide the first steps towards informed mediation of this important and interesting interdisciplinary debate, and our hope is to offer guidance with regard to both the practice of modelling inequality, and the inequality of modelling practice. 1   Introduction   1.1   Econophysics and its discontents   1.2   Against burglar economics 2   Modelling Inequality   2.1   Mainstream economic models for income distribution   2.2   Econophysics models for income distribution 3   Idealizations in Kinetic Exchange Models   3.1   Binary interactions   3.2   Conservation principles   3.3   Exchange dynamics 4   Fat Tails and Savings 5   Evaluation